Factors associated with caesarean section in women giving birth at RSUD dr. Abdul Rivai Berau - Luhwati, Wayan; Hartati, Dwi; Meihartati, Tuti; Purwanti, Heni (Institute of Computer Science (IOCS), 2024)
Caesarean section deliveries can result in a variety of consequences, so they become alternative procedures for childbirth. However, there has been an increase in caesarean section deliveries in the last three months at Dr Abdul Rivai Hospital Berau. It is necessary to know causal factors such as severe pre-eclampsia to address the high rate of caesarean section deliveries, premature rupture of membranes and history of caesarean section deliveries so future pregnant women can prevent caesarean section deliveries by overcoming the problems that occur. This study aimed to determine the factors associated with caesarean section in women giving birth. This study used an analytical survey and a retrospective design. The population was data from women giving birth at Dr Abdul Rivai Hospital Berau from June 01, 2023 to August 31, 2023, numbered 567 people. The Slovin formula obtained a sample of 235 people. Data analysis used chi-square. This study showed that 21.3% of women in labor experienced severe pre-eclampsia, 19.6% had a history of previous caesarean section, 18.3% experienced premature rupture of membranes and 52.3% of caesarean section deliveries. There was a relationship between severe pre-eclampsia and caesarean section (p = 0.001). There was a relationship between previous history of caesarean section and caesarean section (p = 0.006). There was a relationship between premature rupture of membranes and caesarean section (p = 0.043). This indicates Severe pre-eclampsia, premature rupture of membranes and history of caesarean section as factors causing caesarean section. Hospitals expect to provide counseling about maintaining good pregnancies to avoid caesarean sections for pregnant women who have regular health checks.